Pengaruh Motivasi dan Kemampuan Terhadap Kinerja - Luhgiatno Luhgiatno (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
This research study it’s about motivation and capability to work activity at PT. Gelora Fajar Farma. Research problem will be discuss is: 1) How for worker motivation to the work activity. 2)How for worker capability influence to the work activity. 3) How for worker motivation influence and capability to the work activity.The research used 2 models simple regression and 1 model doubled analysis. First model motivation variable as independent variable and work activity variable as dependent variable. Second model capability variable as independent variable and work activity variable as dependent variable.Third model motivation variable and capability as independent variable and work activity variable as dependent variable. Total sample is taking 75 respondent used random sampling by questioner.This researched result is to show that the motivation and capability influential significant according to partial is the work activity which is approved it by ttest.While motivation variable and ability was influence significant according to simultan is the work activity which is approved it by f-test.